THE DETERMINING OF ENTREPRENEURIAL INTENTIONS: A STUDY ON ENTREPRENEURIAL STUDENTS IN JAKARTA - Ravinata, Vellya; Nuringsih, Kartika (International Journal of Application on Economics and Business, 2024)
The unemployment rate in Indonesia is very high due to high population growth resulting in an imbalance between job seekers and available jobs. One approach that can be taken to overcome unemployment is through entrepreneurial mechanisms. However, the number of entrepreneurs in Indonesia is still very low so researchers are interested in conducting research related to variables that can affect entrepreneurial intentions in students at management program of economic faculty and business of Tarumanagara University. It involves entrepreneurship education, subjective norms, and entrepreneurial attitudes. The theory of planned behavior serves as the underlying framework for conducting research. The sampling design was carried out using convenience sampling techniques using a sample of 103 students who were or had taken entrepreneurship courses. Data processing methods are applied utilizing the Partial Least Squares-Structural Equation Modeling approach for data analysis. The results indicate that subjective norms and attitudes toward entrepreneurship positively and significantly influenced entrepreneurial intentions, while the impact of entrepreneurship education, although positive, did not reach statistical significance. These results are as information in developing entrepreneurial education programs on campus.